2015
DOI: 10.1111/cei.12640
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of non-absorbable delayed release 6-mercaptopurine is locally active in the gut, exerts a systemic immune effect and alleviates Crohn's disease with low rate of side effects: results of double blind Phase II clinical trial

Abstract: Summary Therapy for Crohn's disease (CD) with thiopurines is limited by systemic side effects. A novel formulation of fixed‐dose, delayed‐release 6‐mercaptopurine (DR‐6MP) was developed, with local effect on the gut immune system and minimal absorption. The aim of this study was to evaluate the safety and efficacy of DR‐6MP in patients with moderately severe CD compared to systemically delivered 6‐mercaptopurine (Purinethol). Seventy CD patients were enrolled into a 12‐week, double‐blind controlled trial. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…DR‐6MP was safer than Purinethol, with significantly fewer adverse events. There was no evidence of drug‐induced leukopenia in the DR‐6MP group, and a much lower proportion of hepatotoxicity 94 …”
Section: Oral Administration Of Non‐absorbable Delayed‐release 6‐mercmentioning
confidence: 87%
See 2 more Smart Citations
“…DR‐6MP was safer than Purinethol, with significantly fewer adverse events. There was no evidence of drug‐induced leukopenia in the DR‐6MP group, and a much lower proportion of hepatotoxicity 94 …”
Section: Oral Administration Of Non‐absorbable Delayed‐release 6‐mercmentioning
confidence: 87%
“…A novel formulation of low‐dose, delayed‐release 6‐mercaptopurine (DR‐6MP) was developed for oral immune therapy 94 . Pharmacokinetic and proof‐of‐concept open‐label studies showed that DR‐6MP is not absorbed significantly.…”
Section: Oral Administration Of Non‐absorbable Delayed‐release 6‐mercmentioning
confidence: 99%
See 1 more Smart Citation
“…DR 6‐MP was also found to be safer than 6‐MP, with significantly fewer adverse events and no evidence of drug‐induced leucopenia. The proportion of subjects who developed hepatotoxicity was also lower . These data suggest that it is possible to achieve comparable clinical efficacy to parenteral administration using oral administration, but with a safer, non‐absorbable formulation that functions via a different immune‐based mechanism.…”
Section: Introductionmentioning
confidence: 88%
“…On the other hand, the combination of both substances was even more effective, which encourages the use of immunomodulators as combination partners [33]. Moreover, a phase II study was able to demonstrate that a delayed release formulation of 6-mercaptopurine is able to improve the ratio between efficacy and adverse side effects [34]. …”
Section: Approved Substances – State Of the Artmentioning
confidence: 99%